A study on the perception of librarians on property accountability and its applicability to the practice of the library profession - Quintos, Kate Lora M.; Ong, Milagros S. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
Librarians manage the library, as well as give diligent care for the collection and try to secure the collection. They try their very best to perform all their tasks. They serve the patrons to the best of their abilities. This paper aims to disclose the perceptions of librarians to property accountability and its effect to the library service. The threat and occurrence of losses and theft are inevitable in any library. Librarians shoulder the responsibility over their collection called property accountability.
This study is about the effects of property accountability to service library service, the security and the human relations of the librarian. By making the plight of librarians known, the law-making body of the country will be equipped with first-hand information on the matter thus enabling for better and more appropriate laws. The researcher conducted surveys and interviews for the data needed in this research.
The results from the surveys and interviews show that the main thrust of libraries is to give service to its patrons and although there is little control over the collection, open shelves is still preferred by many. In cases of loss and theft, the librarians are more than willing to accept responsibility, if they are the ones who perpetuated the action. They are mature professionals who value service as well self-respect and self-worth. At the moment, they aspire for the protection of the law to shield them from accountability that they are not responsible for. They are vulnerable to property accountability because their shield is not yet made. In conclusion, librarians do their part in the service of the community, even if this entails accountability of the librarians over the losses and incidence of theft of another perpetuator. The librarians are willing to accept the responsibility of property accountability provided that they have taken a part in the execution of the action. The researcher recommends that a bill should be proposed on the issue of property accountability of librarians. This should contain probable instances that could determine the liability of the librarian, allowance for relief, security issues and other related issues concerning property accountability. Existing accountability provisions should be revised in order to address the current situation of the librarians.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Material accountability